Multidimensional fluorescence imaging of biological tissue - Dunsby,C; McGinty,J; French,P (2014)
This chapter aims to review multidimensional fluorescence imaging (MDFI) technology and its application to biological tissue, with a particular emphasis on fluorescence lifetime imaging (FLIM) of biological tissue with examples from our work at Imperial College London. Fluorescence imaging is flourishing tremendously, partly driven by advances in laser and detector technology, partly by advances in labeling technologies such as genetically expressed fluorescent proteins, and partly by advances in computational analysis techniques. Increasingly, fluorescence instrumentation is developed to provide more information than just the localization or distribution of specific fluorescent molecules. Often, fluorescence signals are analyzed to provide information on the local fluorophore environment or to contrast different fluorophores in complex mixtures-as often occur in biological tissue. This trend to higher-content fluorescence imaging increasingly exploits MDFI and measurement capabilities with instrumentation that resolves fluorescence lifetime together with other spectroscopic parameters such as excitation and emission wavelength and polarization, providing image information in two or three spatial dimensions as well as with respect to elapsed time (Figure 18.1). However, caution should be exercised when acquiring such MDFI since photobleaching or experimental considerations usually impose a limited photon budget and/or a maximum image acquisition time and also present significant challenges with respect to data analysis and data management. These considerations are particularly important for real-time clinical diagnostic applications, for higher-throughput assays, and for the investigation of dynamic biological systems (Figure 18.1).